Risk Factors and Manifestations of Food Allergy in Young Children - Khasanova Gulhayo Saipidin kizi (Zien Journals, 2024)
This article highlights the features of the clinical course, etiology of food allergies in young children, depending on the types of feeding.
Keywords: allergies; children; risk factors